A collaborative knowledge management framework for supply chains: A UML-based model approach - Jorge Esteban Hernández; Raúl Poler; Josefa Mula; David Peidro (Journal of Industrial Engineering and Management (JIEM), 2008)
In the most general cases, collaborative activities imply a distributed decision-making process which involves several supply chain nodes. In this paper, by means of a literature review, and by also considering the deficiencies of existing proposals, a collaborative knowledge management UML-based framework supported is proposed. In addition, this proposal synthesizes existing knowledge, and it not only fulfils, but enriches, each component with the modeller's own knowledge.
Keywords: 650; knowledge management; unified modelling language; framework; collaborative supply chain